Optimizing locked nucleic acid/2-O-methyl-RNA fluorescence in situ hybridization (LNA/2OMe-FISH) for bacterial detection - Azevedo, Andreia S. (2018)
Despite the successful application of locked nucleic acid/2-O-methyl- RNA fluorescence in situ hybridization (LNA/2OMe-FISH) procedures for bacteria detection, there is a lack of knowledge on the properties that affect hybridization. Such information is crucial for the rational design of the protocols, especially in multiplex assays. Hence, this work aimed to evaluate the effect of 3 essential factors on the LNA/2OMe hybridization step - hybridization temperature, NaCl concentration and type and concentration of denaturant (formamide, ethylene carbonate and urea). This optimization was performed for 3 Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Citrobacter freundii) and 2 Gram-positive bacteria (Enterococcus faecalis and Staphylococcus epidermidis), employing the Response Surface Methodology and an Eubacteria probe. In general, it was observed that high NaCl concentrations (from 2 to 5M) are beneficial, regardless of denaturant. Urea, formamide and ethylene carbonate are suitable denaturants for FISH applications; but urea provides similar fluorescence signals among the different bacteria. Overall, the results indicate that 2 M of urea, 4 M of NaCl and 62 °C of hybridization temperature would be a proper starting point for multiplex LNA/2OMe-FISH procedures.